1998
DOI: 10.1046/j.1523-1747.1998.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Both Retinoic Acid Receptors α (RARα) and γ (RARγ) Are Able to Initiate Mouse Upper-Lip Skin Glandular Metaplasia

Abstract: Embryonic mouse upper-lip skin explants treated with 16.7 microM all-trans retinoic acid (tRA) give rise to a glandular metaplasia of hair vibrissa follicles; however, at this concentration, tRA can activate not only the three retinoic acid receptors (RARalpha, beta, and gamma), but also the retinoid X receptors (RXRalpha, beta, and gamma) as a consequence of its isomerization to 9-cis retinoic acid. We therefore studied the respective roles of the RXR and RAR by treating RARalpha(-/-), beta(-/-), and gamma(-/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Retinoid pathway activities can induce epithelial metaplasia (Hardy and Bellow, 1978;Blanchet et al, 1998) and appendage phenotypes. When retinoic acid is added before phenotypes are irreversibly determined, scales are converted to feathers in chickens (Dhouailly et al, 1980) and hair germs are converted to glandlike structures in mouse (Hardy et al, 1990).…”
Section: Classical Tissue Recombination Experimentsmentioning
confidence: 99%
“…Retinoid pathway activities can induce epithelial metaplasia (Hardy and Bellow, 1978;Blanchet et al, 1998) and appendage phenotypes. When retinoic acid is added before phenotypes are irreversibly determined, scales are converted to feathers in chickens (Dhouailly et al, 1980) and hair germs are converted to glandlike structures in mouse (Hardy et al, 1990).…”
Section: Classical Tissue Recombination Experimentsmentioning
confidence: 99%
“…The nitro group-substituted HX531 (114) was the most effective antagonist of these para-substituted analogs. Both HX531 (114) and HX539 (115) also attenuated RAR activity in transfection assays by functioning as either a partial agonist or antagonist.…”
Section: Other Selective Retinoidsmentioning
confidence: 96%
“…The nitro group-substituted HX531 (114) was the most effective antagonist of these para-substituted analogs. Both HX531 (114) and HX539 (115) also attenuated RAR activity in transfection assays by functioning as either a partial agonist or antagonist. The N-propyl benzodiazepine HX603 (118) [307] was found to be the most effective RXRselective antagonist in the N-alkyl-substituted series.…”
Section: Other Selective Retinoidsmentioning
confidence: 96%
See 1 more Smart Citation
“…It was shown that RXRα has key roles in hair development and in epidermal keratinocyte proliferation and differentiation [3,84]. The knock-out of the RARα, RARβ, or RARγ genes does not prevent RA-induced mouse upper-lip skin glandular metaplasia, but RARγ knock-out dramatically decreases its ratio [87]. Both RARα and RARγ can initiate a glandular metaplasia, whereas RARβ cannot give rise to any metaplasia, but the following progression of metaplasia requires RARβ, indicating that these receptors have both redundant and unique functions [87].…”
Section: Development Of Skin In Retinoid Signaling Deficient Micementioning
confidence: 99%